Effect of Word Processing Applications to Improving Spelling for Ability Deaf Children in Elementry School - Rifnurrohma A Q; Mohammad Efendi; Henry Praherdhiono (Department of Special Education, 2017)
This study aimed to determine the effect of word processing application on learning outcomes spelling ability p there is a deaf child in primary school. The research is a quantitative research, with this type of research Pre-Experimental with One-Group Pre-test Post-test Design , the subject of research amounted to 4 people . Based on the hypothesis testing results obtained 10.98> 3182 , so there is a significant influence on the use of a word processing application on spelling ability in deaf children.